1976
DOI: 10.1055/s-0028-1097702
|View full text |Cite
|
Sign up to set email alerts
|

AUSBILDUNG UND VERTEILUNG VON ISOFLAVON–7–O–β–GLYKOSID SPEZIFISCHEN β–GLYKOSIDASEN INCICER ARIETINUM

Abstract: Various P-glycosidases, specific for the hydrolysis of isoflavone 7-O-p-glycosides, have been detected in the garbanzo bean, C i c e r a r i e t i n u m L. ,6-Monoglucosidases are present within the different plant organs in comparable activity whereas j3-diglycosidases are found in the leaves only. Both ,ô-glycosidase activities develop in the earliest States of plant growth, probably by protein de novo synthesis. A correlation between p-glycosidases and isofïavones present in garbanzo bean plants is discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The MALDI-TOF analysis also showed sequences of the five resultant peptide sequences are closest to those of β-glucosidase from C icer arietinum (Chickpea). The β-glucosidase from the C. arietinum has also been reported to exhibit the isoflavones conjugates hydrolyzing properties [24] confirming the functional nature of the enzyme purified from the Guar seeds.
Fig. 6MALDI-TOF and MS analysis of purified enzyme ICHG showed maximum similarity with isoflavone-7-O-glucoside-specific beta-glucosidases from Cicer arietinum.
…”
Section: Resultsmentioning
confidence: 69%
“…The MALDI-TOF analysis also showed sequences of the five resultant peptide sequences are closest to those of β-glucosidase from C icer arietinum (Chickpea). The β-glucosidase from the C. arietinum has also been reported to exhibit the isoflavones conjugates hydrolyzing properties [24] confirming the functional nature of the enzyme purified from the Guar seeds.
Fig. 6MALDI-TOF and MS analysis of purified enzyme ICHG showed maximum similarity with isoflavone-7-O-glucoside-specific beta-glucosidases from Cicer arietinum.
…”
Section: Resultsmentioning
confidence: 69%
“…The FGG activity parallels flavone accumulation. As described for the /3-glucosidase from Cicer arietinum (23), it decreases after having reached a maximum at stage IV. Kinetic studies revealed a significant preference for monoglucosides /3-linked at the 7-0-position of the flavonoid skeleton.…”
Section: The Addition Of Heavy Metal Ions Such Asmentioning
confidence: 67%